2017
DOI: 10.1680/jbibn.16.00012
|View full text |Cite
|
Sign up to set email alerts
|

The elephant in the room: biomimetics and sustainability?

Abstract: Biomimetics, with diverse origins, has generated a ‘biomimetic promise’ of sustainable design solutions. This promise posits that biological systems are inherently sustainable and emulating these time-tested patterns will result in optimal sustainability characteristics. However, this has rarely been empirically explored and there is little understanding of how biomimetic practitioners are assessing sustainability impacts. This paper examines connections between biomimetic innovation and sustainability theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…As an inter-and transdisciplinary topic, several perspectives exist about what learning from nature actually is (see, e.g., [1]), how it should be performed, and how it may develop [3,7,12,13]. This paper represents one such view and intends to contribute to the field.…”
Section: Terminologymentioning
confidence: 99%
See 1 more Smart Citation
“…As an inter-and transdisciplinary topic, several perspectives exist about what learning from nature actually is (see, e.g., [1]), how it should be performed, and how it may develop [3,7,12,13]. This paper represents one such view and intends to contribute to the field.…”
Section: Terminologymentioning
confidence: 99%
“…Example: Biological materials with special mechanical properties to inspire biomimetic devices [22]. 4 A means for sustainable solutions [1,12,[23][24][25] Teaching will refer to any curriculum, learning objective, and teaching environment based in academia. The audience for this will be referred to as students.…”
Section: Terminologymentioning
confidence: 99%
“…BM design is defined as 'an intended emulation of nature life solutions for solving contemporary challenges' (Cohen & Reich, 2016, p. 3). It encourages the observation of the ways in which nature solves problems in order to create novel solutions (Mead & Jeanrenaud, 2016). The premise of BM design is to use nature as a model, measure and mentor (Benyus, 2002).…”
Section: Taking Inspiration From Naturementioning
confidence: 99%
“…more opportunities (in relation to this, refer to the systemic design approach discussed in Chapter 10). In addition, there is not an established system of accountability for BM design in sustainability-oriented innovation, therefore it is unclear how BM design practice relates to sustainability agendas and how sustainability is addressed and assessed by practitioners (Mead & Jeanrenaud, 2016). Benyus (2002) indicated that the full potential of BM design cannot be realised unless it becomes integrated into an economic system that itself mimics living systems.…”
Section: 63 Benefits and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation